(untitled) (Physical Education, Health and Social Sciences, 2025)
Sufficient knowledge required to deal with emergencies at the accident site may not be found in most nursing students due to the lack of effective first aid training in most nursing education curricula. This study aims to assess and evaluate the level of knowledge among nursing students in providing first aid care. This cross-sectional study was conducted in August 2023 among 152 nursing students. The data was collected using an electronic questionnaire that was published on social media platforms. Based on the scores obtained for each clinical scenario requiring first aid, general knowledge was classified as good or weak in order to obtain the best result, a number of measures were taken. Statistical analysis indicated that Academic year and Academic specialization have a significant effect on the level of knowledge, whereas demographic background (gender, university, marital status housing status, work status, financial condition), reading, hearing, or receiving training in first aid have no effect on it. The level of knowledge among students of private nursing colleges in Swabi, KPK, Pakistan in providing first aid care is somewhat limited. Therefore, first aid courses should be made more accessible to these students, and their effectiveness should be ensured and maintained through frequent updates. Moreover, more attention should be placed on publicizing first aid knowledge in a way that makes life-saving procedures attainable to anyone, anytime and anywhere.